이상기후 대비 중소규모 저수지 비상대처계획 운영에 따른 효율적인 주민대피계획: 네트워크 분석을 통한 주민 대피결과를 바탕으로 - 최병한; 원동현; 홍재주; 문수진; Choi, Byoung Han; Won, Dong Hyun; Hong, Jae Joo; Moon, Soo Jin (Journal of Korea Water Resources Association, 2024)
This study aims to address the shortcomings in evacuation planning for residents downstream of small and medium-sized reservoirs with a capacity of less than 200,000 cubic meters. using the Yugum Reservoir in Gangdong-myeon, Gyeongju City, as a case study, the research proposes evacuation area planning and disaster response measures based on spatial network analysis. Flood prediction simulations and quantitative data analysis were employed to design evacuation routes that account for walking characteristics, terrain, and accessibility, thereby establishing a resident-centered evacuation plan, including considerations for vulnerable populations. This approach complements the limitations of existing evacuation plans, which are primarily focused on physical responses, by highlighting the importance of flexible and effective evacuation strategies grounded in precise data analysis. The findings are expected to contribute to the development of a swift and efficient response system prioritizing resident safety during extreme weather and disaster scenarios. Moreover, this study is anticipated to offer significant direction for advancing disaster response systems and enhancing resident centered safety. 본 연구는 20만 세제곱미터 미만의 중소규모 저수지 하류부 주민 대피계획의 미흡한 문제를 해결하고자, 경상북도 경주시 유금저수지를 대상으로 공간 네트워크 분석을 활용한 대피지역 설정 및 재해대응 방안을 제시하였다. 침수 예측 시뮬레이션과 정량적 데이터 분석을 통해 보행 특성, 지형, 접근성을 반영한 대피 경로를 설계하였으며, 취약계층을 포함한 주민 중심의 대피계획을 마련하였다. 이에 기존 물리적 대응 중심의 대피계획이 가진 한계를 보완하고, 정밀 데이터 기반의 유연하고 효과적인 대피 전략 수립의 중요성을 확인하였다. 이는 이상기후와 재난 상황에서 주민 안전을 최우선으로 하는 신속하고 효율적인 대응 체계 구축에 기여할 뿐만 아니라, 재난 대응 체계의 고도화와 주민 중심의 안전 확보에 중요한 방향성을 제공할 것으로 기대해본다.